Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1175/jas-d-19-0264.1
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Wave Excitation during the Coastal Transition of an Extreme Katabatic Flow in Antarctica

Abstract: The offshore extent of Antarctic katabatic winds exerts a strong control on the production of sea ice and the formation of polynyas. In this study, we make use of a combination of ground-based remotely sensed and meteorological measurements at Dumont d’Urville (DDU) station, satellite images, and simulations with the Weather Research and Forecasting Model to analyze a major katabatic wind event in Adélie Land. Once well developed over the slope of the ice sheet, the katabatic flow experiences an abrupt transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…As reported by Vignon et al (2020) using station measurements, there is a relatively quiescent period before the 9th of August 2017 with stable wind speed, wind direction and air temperature recorded at DDU. The situation dramatically changes on the 9th when the katabatic flow rapidly strengthens and very high wind speeds are reported at DDU in the first half of the 10th.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…As reported by Vignon et al (2020) using station measurements, there is a relatively quiescent period before the 9th of August 2017 with stable wind speed, wind direction and air temperature recorded at DDU. The situation dramatically changes on the 9th when the katabatic flow rapidly strengthens and very high wind speeds are reported at DDU in the first half of the 10th.…”
Section: Resultsmentioning
confidence: 62%
“…At 1200 hrs on the 10th, there is a sudden drop in the wind speed, following which the wind becomes gusty but on average remains slower than the previous day. Vignon et al (2020) showed that the abrupt deceleration of the katabatic flow is due to excitation of gravity waves and the enhanced friction induced. nested domains with different resolutions, particularly for wind speeds and direction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, Dumont D'Urville is located on Petrel Island and approximately 5 km from the main ice sheet. It is subject to strong katabatic winds, which flow from the Antarctic interior, which can also generate gravity waves (Vignon et al, 2020). It is also expected, from previous studies (Moffat-Griffin et al, 2011, 2013, that those stations close to the Drake Passage will see greater levels of gravity wave activity as this is where the main gravity wave "hotspot" is located.…”
Section: Radiosonde Datamentioning
confidence: 89%